Central Asian Factor in India-Pakistan Competition (1990-2019) - Rano Almamatovna, Tuychiyeva (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this article is to provide literature on three main periods (1990-2001, 2001-2010, 2010-2019) on the relationship between India, Pakistan and Central Asia over the past 30 years, including regional security and study and analyse groups based on regional, political, economic, and ethnic-religious issues learned from them. The article also examines the relationship between India and Pakistan, the causes and effects of the unresolved regional, political and religious conflicts and their impact on the geopolitical, economic and social spheres in Central and South Asia. The relations of the two countries and the interests of the United States, Russia, China, Afghanistan and Central Asia, and Uzbekistan in particular, have been studied. The article consists of annotation, keywords, introduction, main part, conclusion and list of references. Problem-chronological, comparative and general scientific analysis methods were used in writing the article. The novelty is that today India-Pakistan relations have been greatly influenced by the process of comprehensive modernization of Central Asian countries in international relations, but it has not been studied in Uzbekistan in the years of independence. The literature on this topic is grouped according to its regional, chronological, and problematic features and provides the necessary conclusions.